Comparative Evaluation Of Total Phenolics And Free Radical Scavenging Activity Of The Aqueous Extracts Of Labisia Pumila Var. Alata From Malaysia And Indonesia - Iwansyah, Ade Chandra; M. M., Yusoff (2011)
Abstract— Functional food and beverage companies are touting the presence of antioxidants in their products in response to consumer interest in the potential health benefits of antioxidants in the diet. Labisia pumila (LPva) or “Kacip Fatimah” is a popular supplement in the Malaysian functional food and beverage market. Today, information on its bioactive compounds remains scarce. A comparative evaluation of total phenolics and free radical scavenging activity of the aqueous extract of LPva were studied using Folin – Ciocalteu assay, aluminum chloride assay, ferric ion reducing power assay and DPPH (1,1-diphenyl-2-picrylhydrazyl) scavenging assay. The results of total phenolics showed that LP from Tilu Mountain- Bogor (LPvaT) contained the highest average of total phenolics. The ratio of total flavonoids/total phenolics (TFC/TPC) of LP from Halimun-Salak Mountain, Bogor (LPvaB) with is 0.27 and contained the highest average of total flavonoids. Antioxidant activity by FRAP assay shows that LPvaT contained the highest average of ability to reduce the ferric ion-TPTZ complex. DPPH assay showed that EC50 of LPvaT (78.79 μg/mL) was lowest. Based on these values, LPvaT is found to have the highest antioxidant activity.